Shining through dark clouds : 1870-1871 - Dye, Ginny (Dye, Ginny. Bregdan chronicles series, 2019)
Another chapter in the lives of Carrie, Janie, Rose and Moses, Florence Robinson, and Felicia as they work to rebuild their lives in Virginia during the United States' Reconstruction.